Factors of Students’ Speaking Anxiety in the 3rd Level of ESC in Higher Institution - Kushadi, Nadhila Amalia (RETAIN, 2021)
This research aims to identify the dominant factors in ESC students’ anxiety and to examine what aspects influence the students’ anxiety. This study was conducted at Universitas Negeri Surabaya. The researcher used two instruments in this research, which are questionnaire and interview. The questionnaire was adapted from Horwitz, Horwitz and Scope (1986) and interview were to obtain information about the aspects that influence students’ level of anxiety during speaking. The participant of this study was from ESC students’ in the 3rd level of English Department at Universitas Negeri Surabaya. The researcher took 20 students in the 3rd level of ESC. This research used a descriptive quantitative as the research design. According to the data obtained, the researcher found the dominant factor of ESC students’ in the 3rd level is “fear of negative evaluations”. The researcher also found the aspects influence students’ speaking anxiety because they had a lack of confidence, vocabulary and sometimes they did not know how to pronounce some words. However, they agreed that ESC could improve their self-confidence while speaking. Keywords: Speaking, Anxiety, English Speaking Community